EFEKTIFITAS PENGELOLAAN DAN PEMANTAUAN LINGKUNGAN MASJID AGUNG KABUPATEN KEPULAUAN SELAYAR - Fikruddin, Muhammad; Akrim, Djusdil; Jumadil, Jumadil; Syaiful, Andi Zulfikar; Anggraini, Nani; Yacub, Nur' Aini (Program Studi Teknik Lingkungan Universitas Bosowa, 2024)
Selayar Islands Regency is one of the areas in which there are various kinds of diversity, ethnicity, customs and culture owned by the community. As one of the Archipelagic Regencies in South Sulawesi, it has an amazing historical background, maritime culture and historical journey of the spread of Islam. This study discusses the effectiveness of environmental management and monitoring of the Grand Mosque of the Selayar Islands Regency. This research method is qualitative-descriptive, research data collection is done by using observation and documentation. The results show that the effectiveness of environmental management and monitoring is largely determined by the role of the management team that conducts self-monitoring and monitoring per month.